Sovereign funds and their role in the global economy - هزاع سلمان; محمد محمد (آداب الكوفة, 2012)
Sovereign funds are not a new phenomenon in the global financial arena, as these funds go back to the fifties of the last century. These funds have gained increasing importance in the international monetary and financial system, especially after their success in pumping large capitals into European and American banks, until they have now become the latest and most important issue in the field of money and finance in the world, as they have contributed to the rescue of many Western financial institutions that incurred losses. Fatal as a result of the American mortgage crisis